Public support for cancer prevention and care policies in Aotearoa New Zealand: methods of a national survey - Bronwen McNoe; Andrew Gray; Ella Iosua; Rana Peniamina; Louise Signal (New Zealand Medical Journal, 2026)
aim: Our aim was to describe the shared elements involving design, sampling, weighting and analytic framework of a national survey of public views on cancer prevention and care in Aotearoa New Zealand for the seven topic-specific brief reports in this issue of the New Zealand Medical Journal. methods: We conducted a nationwide, self-administered, cross-sectional online survey of adults aged 18 years or older between November and December 2025. Participants were recruited via an established online research panel using quota sampling aligned to 2023 Census benchmarks for age, gender and ethnicity, with additional recruitment to ensure adequate Māori and Pacific representation. The survey assessed public views across cancer prevention, vaccination, early detection, treatment and care, alongside political and advocacy contexts. Design and poststratification weights were applied to align the sample with population benchmarks for combinations of age groups, gender and Māori ethnicity. Analyses were descriptive and stratified by key socio-demographic characteristics, namely age, gender, ethnicity and voting intentions. results: A total of 1,635 participants completed the survey. The effective weighted sample size was 1,161, corresponding to a worst-case margin of error of ±2.9% overall. conclusion: This paper provides methods for a series of policy-relevant brief reports that examine public support for cancer prevention and care in Aotearoa New Zealand.